(untitled) (The Pakistan Development Review, 1995)
Are devaluations contractionary? This question has been with us for a long time. The conventional Keynesian economist holds the view that if devaluation is demandexpansionary, then both output and balance-of-payments will improve with devaluation. Experience, however, shows contrary outcomes. For example, Sheehy (1986), who has covered 16 Latin American countries, concluded that devaluation was highly contractionary in these countries. Edwards (1986), on the other hand, has covered 12 less developed countries (LDCs) and found that devaluations are contractionary in the impact period, while in the long-run they all become neutral. Hamarious (1989) has used the data for the periods 1953-73 and 1975-84 and has covered twenty-seven countries and six devaluation episodes to study the effects of devaluations upon prices and the trade balance. He found that in over 80 percent of the cases, devaluation causes a net improvement in the trade balance both in the impact period and in the middle period. The study concluded that the effects of devaluation upon the trade balance last for two to three years. Such results seriously challenge the theoretical results derived by the conventional economist.